Potential role of B- and NK-cells in the pathogenesis of pediatric aplastic anemia through deep phenotyping - Vissers, Lotte T. W.; van Ostaijen-ten Dam, Monique M.; Melsen, Janine E.; van der Spek, Yanna M.; Kemna, Koen P.; Lankester, Arjan C.; van der Burg, Mirjam; Mohseny, Alexander B. (Frontiers in Immunology, 2024)
Pediatric patients with unexplained bone marrow failure (BMF) are often categorized as aplastic anemia (AA). Based on the accepted hypothesis of an auto-immune mechanism underlying AA, immune suppressive therapy (IST) might be effective. However, due to the lack of diagnostic tools to identify immune AA and prognostic markers to predict IST response together with the unequaled curative potential of hematopoietic stem cell transplantation (HSCT), most pediatric severe AA patients are momentarily treated by HSCT if available. Although several studies indicate oligoclonal T-cells with cytotoxic activities towards the hematopoietic stem cells, increasing evidence points towards defective inhibitory mechanisms failing to inhibit auto-reactive T-cells. We aimed to investigate the role of NK-and B-cells in seven pediatric AA patients through a comprehensive analysis of paired bone marrow and peripheral blood samples with spectral flow cytometry in comparison to healthy age-matched bone marrow donors. We observed a reduced absolute number of NK-cells in peripheral blood of AA patients with a skewed distribution towards CD56 bright NK-cells in a subgroup of patients. The enriched CD56bright NK-cells had a lower expression of CD45RA and TIGIT and a higher expression of CD16, compared to healthy donors. Functional analysis revealed no differences in degranulation. However, IFN-γ production and perforin expression of NK-cells were reduced in the CD56bright -enriched patient group. The diminished NK-cell function in this subgroup might underly the auto-immunity. Importantly, NK-function of AA patients with reduced CD56bright NK-cells was comparable to healthy donors. Also, B-cell counts were lower in AA patients. Subset analysis revealed a trend towards reduction of transitional B-cells in both absolute and relative numbers compared to healthy controls. As these cells were previously hypothesized as regulatory cells in AA, decreased numbers might be involved in defective inhibition of auto-reactive T-cells. Interestingly, even in patients with normal distribution of precursor B-cells, the transitional compartment was reduced, indicating partial differentiation failure from immature to transitional B-cells or a selective loss.Our findings provide a base for future studies to unravel the role of transitional B-cells and CD56bright NK-cells in larger cohorts of pediatric AA patients as diagnostic markers for immune AA and targets for therapeutic interventions.